PENGARUH KARAKTERISTIK INTERNAL DAN EKSTERNAL AUDITOR YANG MENDORONG DILAKUKANNYA PREMATURE SIGN OFF DALAM PENDEKATAN ETIKA - DP, Emrinaldi Nur; Wiguna, Meilda Wiguna (MEDIA EKONOMI & TEKNOLOGI INFORMASI, 2013)
This research intends to analyze the effect of time pressure, audit risk, materiality, and Locus of control of auditor that can affect the premature sign offprocedures.The object of this research is auditors.The data obtain by questionnaire which directly send to 69 auditors who work in 15 Public Accountant FirmsÂ  from three Provinces (Riau, Kepulauan Riau, and Sumatera Barat). Analytical model which used for this research to get the effect of independen variables to dependent variables is logisticÂ  regresion. Premature Sign off as dependent variable is a dummy variable which showed the result for ten question of PSO level. Based on research concluded that risk, materiality, and auditorsâ Locus of control could affect the premature audit procedures sign off. It can be proven by the second,third, and the fourth hypothesis. But time pressure has no affect the premature audit procedures sign off as predicted in first hypothesis .